Role of comprehensive care in Fontan survivors: A multidisciplinary team approach. (March 2018) - Di Maria, Michael V.; Menon, Shaji C.
Abstract: The current standard management strategy for patients born with single ventricle heart disease includes a series of palliative surgeries, culminating in the Fontan operation. With the recognition that survivors of Fontan palliation are at risk for developing a wide breadth of complications, spanning multiple different organ systems, interest in developing multidisciplinary teams dedicated to the care of these patients has emerged. The key element of this approach is the recognition that the care paradigm in which Fontan patients simply see their cardiologist annually for an echocardiogram is no longer adequate or appropriate. Leaving behind the passive, reactive approach, screening for pathology in the early stages will likely afford an opportunity for intervention in some cases, or at minimum closer surveillance in situations where therapies lag behind diagnostic testing. A multidisciplinary standardized approach to screening and evaluation by subspecialists is critical in surveillance and management of Fontan associated multisystem aberrations. Highlights: Fontan operation remains the current standard management strategy for patients born with single ventricle heart disease. Following Fontan, there is increasing evidence for the broad range of pathology spanning nearly every organ system. The natural history and progression of Fontan associated multisystem disease remains unclear and will need further investigation. A multidisciplinary standardized approach is critical in surveillance and management of Fontan survivors.